An institutional experience of pre‐emptive liver transplantation for pediatric primary hyperoxaluria type 1. (8th April 2016) - Khorsandi, Shirin Elizabeth; Samyn, Marianne; Hassan, Akhila; Vilca‐Melendez, Hector; Waller, Simon; Shroff, Rukshana; Koffman, Geoff; Van't Hoff, William; Baker, Alastair; Dhawan, Anil; Heaton, Nigel
Abstract: Primary hyperoxaluria type 1 (PH1) is an inherited metabolic disease that culminates in ESRF. Pre‐emptive liver transplantation (pLTx) treats the metabolic defect and avoids the need for kidney transplantation (KTx). An institutional experience of pediatric PH1 LTx is reported and compared to the literature. Between 2004 and 2015, eight children underwent pLTx for PH1. Three underwent pLTx with a median GFR of 40 (30–46) mL/min/1.73 m 2 and five underwent sequential combined liver‐kidney transplantation (cLKTx); all were on RRT at the time of cLKTx. In one case of pLTx, KTx was required eight and a half yr later. pLTx was performed in older (median 8 vs. 2 yr) and larger children (median 27 vs. 7.75 kg) that had a milder PH1 phenotype. In pediatric PH1, pLTx, ideally, should be performed before renal and extrarenal systemic oxalosis complications have occurred, and pLTx can be used "early" or "late." Early is when renal function is preserved with the aim to avoid renal replacement. However, in late (GFR < 30 mL/min/1.73 m 2 ), the aim is to stabilize renal function and delay the need for KTx. Ultimately, transplant strategy depends on PH1 phenotype, disease stage, child size, and organ availability.